Internalization Of Multicultural Islamic Education Values In Shaping Moderate Attitudes At Islamic Boarding School - Fadhlullah Makmun; Muhammad Fahmi Hidayatulllah; Imam Safi’i (Institut Agama Islam An-Nawawi Purworejo, 2025)
The phenomenon of increasing intolerance and radicalism emphasizes the importance of strengthening religious moderation through Islamic education, particularly in Islamic boarding schools (pesantren). This study aims to analyze the process of internalizing multicultural Islamic educational values ​​in shaping moderate attitudes at the Al-Amien Prenduan Islamic Boarding School. Using a qualitative approach with a case study design, data were collected through participant observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. The results indicate that the values ​​of equality and justice, tolerance and plurality, unity and brotherhood, nationalism, and anti-radicalism are internalized through ta'aruf (introduction to religious teachings), habituation, Jimbaz (religious gatherings), mujadalah (religious guidance), and the exemplary behavior of kyai (Islamic religious teachers). This process results in an inclusive, tolerant, and moderately religious pesantren environment. These findings contribute to the development of Islamic multicultural education theory and strengthen the role of pesantren as agents of social and cultural moderation. Future research is recommended to expand the scope to other pesantren for more comprehensive results.